Transformation of Child Status: From Adopted Child to Child in Review of Positive Law and Islamic Law - Nadiya, Siti; Syaidah Nasution, Zahratus; Abdulah Pakarti, Muhammad Husni (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
Adoption refers to the act of taking a child who is not your biological child and making him your own child. The process of adopting a child must be carried out through legal procedures. When adopting a child, it is necessary to pay attention to existing law, namely from an Islamic legal perspective and from a state legal perspective. In this research, the law and the process of adopting a child are discussed according to Islam and state law. This research uses a library study method where the researcher relies on sources of information from literature as the main source. This research focuses on analyzing existing data or texts, not field data or information obtained directly from experience or eyewitnesses. Researchers only interact with sources available in the library or existing secondary data. The results of this study reveal the Islamic view of someone adopting a child and what laws apply in the process of adopting a child.